The Effect of Counseling with Video Media and Lecture Methods on the Level of Adolescent Reproductive Health Knowledge - Evert Candra; Nilam Noorma; Hesti Prawita Widiastuti (Formosa Journal of Science and Technology, 2023)
Adolescence is the age most vulnerable to reproductive health problems such as early pregnancy, unsafe abortion, sexually transmitted infections, sexual harassment and rape. The purpose of this study was to determine the effect of counseling using video media and lecture methods on the level of knowledge of adolescent reproductive health at SMAN 4 Sendawar. This type of quantitative research uses a quasi-experimental research design with a pretest-posttest design with a control group design. The population in this study were all 67 students of SMAN 4 Sendawar, the total sample was 60 respondents: 30 video groups and 30 lecture groups. The sampling method used is total sampling with 7 people from the total population used as reserves. The data analysis technique used univariate analysis, paired sample t-test and also the frequency distribution, while the bivariate analysis used an independent sample t test. The results of hypothesis testing using the independent sample t test obtained tcount > ttable (2.763 > 2.001) and the significance value was less than 0.05 (p=0.008 <0.05). Then H0 is rejected while Ha is accepted, so there is an effect of giving counseling using video media and the lecture method on the level of knowledge of adolescent reproductive health at SMA Negeri 4 Sendawar. Counseling with video media has a greater effect on the level of knowledge of adolescent reproductive health compared to the lecture method.